Healthcare professionals’ perspectives on medicine prescribing, vaccination, and alternative therapies in pregnancy and breastfeeding: A qualitative study from Catalonia, Spain - Berta Munné-Barellas; Andrea García-Egea; Maria Giner-Soriano; Cristina Vedia-Urgell; Cristina Martínez-Bueno; Cristina Aguilera; Lina Camacho-Arteaga; Marta Lestón-Vázquez; Ainhoa Gómez Lumbreras; Laura Medina-Perucha (PLoS ONE, 2026)
Introduction Healthcare professionals (HCP) encounter a multitude of challenges regarding the utilisation of medicines, vaccines, and alternative therapies in pregnant and breastfeeding women (PBW). Objective The objective of this study was to explore the experiences, beliefs, and attitudes of HCP toward prescribing medicines, vaccines, and alternative therapies during pregnancy and breastfeeding in Catalonia, Spain. Methods This study employed a qualitative methodology, guided by a gender-based perspective. Three discussion groups were conducted, with the participation of 21 HCP during February 2024. Sampling was intentional, purposive designed to ensure discourse diversity. Recruitment was conducted through key contacts in public primary healthcare centres, sexual and reproductive health care centres, hospital settings in Catalonia, using snowball techniques. The data were analysed using thematic analysis. Results The challenges encountered by HCP who provide care to PBW are numerous and vary depending on the healthcare speciality area. Family physicians and nurses identified a lack of training in obstetrics as a factor contributing to difficulties in prescribing medicines. Midwives emphasised the importance of monitoring and follow-up during pregnancy, especially in cases where an adaptation of medication is required, while gynaecologists drew attention to the challenges posed by an increase in medication avoidance. HCP expressed concerns about the safety of the COVID-19 vaccine, as opposed to the greater safety of evidence of pertussis and influenza vaccines. The use of alternative therapies may lead to potential complications during consultations, as some users do not disclose their use. Conclusions This study underscores the challenges encountered by HCP in drug prescriptions, complementary medicine, and vaccination during pregnancy and breastfeeding, considering HCP differences between specialities. Additionally, the study emphasises the difficulties associated with dual follow-up cases and the significance of establishing trusting relationships with users and shared decision-making processes or a good medication adherence. Patient or Public Contribution HCP have participated sharing their experience in prescribing medication and recommendations on vaccines and alternative medicine. The results of this study can be used to effect change in the practice of HCP.